2021
DOI: 10.1186/s12893-021-01369-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between preoperative 25-OH vitamin D levels and postoperative complications in patients undergoing colorectal cancer surgery

Abstract: Background Determining the modifiable risk factors for postoperative complications is particularly significant in patients undergoing colorectal surgery since those are associated with worse long-term outcomes. Methods Consecutive newly diagnosed 104 colorectal cancer patients were prospectively included in this single-center observational study. Preoperative serum 25-OH vitamin D levels were measured and analyzed for infectious and postoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…In animal models, it could suppress bacterial translocation in the intestinal lumen (25). Another report indicates vitamin D is associated with muscle mass, and low vitamin D level is one of the risk factors of postoperative complications (26). The blood testing for such nutritional deficiencies would be important to reduce muscle mass loss and complication after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, it could suppress bacterial translocation in the intestinal lumen (25). Another report indicates vitamin D is associated with muscle mass, and low vitamin D level is one of the risk factors of postoperative complications (26). The blood testing for such nutritional deficiencies would be important to reduce muscle mass loss and complication after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were stratified based on preoperative vitamin D levels, using a threshold of 20 nmol/L. Researchers in this study observed a higher risk of infection in patients with lower vitamin D levels, an outcome that appeared independent of other variables [ 20 ]. Despite utilizing a slightly lower vitamin D deficiency threshold, this study parallels our observations and extends the relevance of vitamin D levels across various surgical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is associated with muscle mass and muscle strength. Additionally, hypovitaminosis D was found to be correlated with increased risk of postoperative complications 78 79. It will be supplemented daily according to the blood sample values: 1000 U/day for patients with vitamin D deficiency (25-hydroxy-vitamin D <50 nmol/L) and a one-off substitution of 150 000 U for patients with severe vitamin D deficiency (25-hydroxy-vitamin D <25 nmol/L) 80…”
Section: Methodsmentioning
confidence: 99%